Islamic Creed Education in Facing the Modern Century - Multazom (Journal of Contemporary Islamic Primary Education, 2025)
Islamic faith education is crucial for students due to the negative impacts of globalization that can affect their character. This study aims to discuss the role of Islamic faith education in facing the challenges of the modern era. This research is descriptive qualitative and supported by literature review. The research was conducted directly in the field using a descriptive qualitative approach that integrates hands-on practice, collaboration, and art methods. The results show that Islamic faith education plays a crucial role in forming a strong foundation of faith and piety for students. Furthermore, this education not only helps understand Islamic values but also serves as a bulwark against negative influences that threaten moral values. Awareness of the importance of Islamic faith education demonstrates that its role is not only vital in facing the challenges of the times but also in shaping a generation strong in spirituality and morality, capable of facing ever-changing dynamics.